2016
DOI: 10.1080/02643294.2016.1147426
|View full text |Cite
|
Sign up to set email alerts
|

Toward a brain-based componential semantic representation

Abstract: Componential theories of lexical semantics assume that concepts can be represented by sets of features or attributes that are in some sense primitive or basic components of meaning. The binary features used in classical category and prototype theories are problematic in that these features are themselves complex concepts, leaving open the question of what constitutes a primitive feature. The present availability of brain imaging tools has enhanced interest in how concepts are represented in brains, and accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
392
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(412 citation statements)
references
References 218 publications
(300 reference statements)
16
392
1
3
Order By: Relevance
“…Abstractness in the left superior ATL has been consistently reported in the literature (Binder et al, 2009;Wang et al, 2010). Abstract words differ from concrete words in a wide range of dimensions, including various types of semantic (e.g., higher loadings on social and emotional contents, lack of sensory referents) and linguistic features (e.g., heavier reliance on linguistic information; Barsalou & Wiemer-Hastings, 2005;Binder et al, 2016;Kousta et al, 2011;Paivio, 2013;Recchia & Jones, 2012;Wang et al, 2018). Researchers observing social effects in the ATL have speculated that the abstractness in the left ATL may be driven by the use of social words as abstract stimuli (Skipper et al, 2011;Zahn et al, 2007), that is, reflecting a social effect rather than an abstractness effect.…”
Section: Abstractness In the Left Superior Atlmentioning
confidence: 92%
See 3 more Smart Citations
“…Abstractness in the left superior ATL has been consistently reported in the literature (Binder et al, 2009;Wang et al, 2010). Abstract words differ from concrete words in a wide range of dimensions, including various types of semantic (e.g., higher loadings on social and emotional contents, lack of sensory referents) and linguistic features (e.g., heavier reliance on linguistic information; Barsalou & Wiemer-Hastings, 2005;Binder et al, 2016;Kousta et al, 2011;Paivio, 2013;Recchia & Jones, 2012;Wang et al, 2018). Researchers observing social effects in the ATL have speculated that the abstractness in the left ATL may be driven by the use of social words as abstract stimuli (Skipper et al, 2011;Zahn et al, 2007), that is, reflecting a social effect rather than an abstractness effect.…”
Section: Abstractness In the Left Superior Atlmentioning
confidence: 92%
“…For stimulus selection, we collected ratings of 633 two-character Chinese nouns on the following three properties: Sociality (how often the meaning of a noun involves an interaction between people (Binder et al, 2016;Lin et al, 2015), 1 = never, 7 = always), valence (1 = negative, 4 = neutral, 7 = positive), and concreteness (1 = very abstract; 7 = very concrete). For stimulus selection, we collected ratings of 633 two-character Chinese nouns on the following three properties: Sociality (how often the meaning of a noun involves an interaction between people (Binder et al, 2016;Lin et al, 2015), 1 = never, 7 = always), valence (1 = negative, 4 = neutral, 7 = positive), and concreteness (1 = very abstract; 7 = very concrete).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the embodied view, evidence from neuroscience demonstrated that much of the conceptual knowledge associated with perception and action was represented and distributed in regions in the ventral and lateral temporal cortex that overlapped with neural substrates responsible for perceiving and acting (Binder et al, 2016;Barsalou, 2008;Martin, 2007;Martin & Chao, 2001;Humphreys & Price, 2002;Pulvermüller et al, 2005;Vigliocco et al, 2004). However, evidence from other neuroimaging studies also corroborated the Domain Specificity account.…”
Section: Domain Specificity and Embodied Cognitionmentioning
confidence: 81%